2001
DOI: 10.1097/00000637-200106000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Fingertip Replantation at or Distal to the Nail Base: Use of the Technique of Artery-Only Anastomosis

Abstract: The authors describe the functional and aesthetic results of microsurgical replantation of 21 fingertip amputations at or distal to the nail base-namely, zone I amputations. There were 15 male and 6 female patients, with an average age of 26 years (age range, 1-41 years). Replantations were performed using the anastomosis of the artery-only technique, with neither vein nor nerve repair. Venous drainage was provided by an external bleeding method with a fish-mouth incision in "distal" zone I amputations for app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 32 publications
2
45
0
2
Order By: Relevance
“…Reported success rates of fingertip replantation ranges are from 70 to 90% [4][5][6][7]. The degree of tissue damage and technical aspects influence these numbers, but we have achieved a replantation rate similar or better to that of these reports.…”
Section: Discussionsupporting
confidence: 60%
“…Reported success rates of fingertip replantation ranges are from 70 to 90% [4][5][6][7]. The degree of tissue damage and technical aspects influence these numbers, but we have achieved a replantation rate similar or better to that of these reports.…”
Section: Discussionsupporting
confidence: 60%
“…Good sensory recovery was reported even in those cases without nerve repair in previous studies. 37,43,45,50 In this study, of the 67 patients with a follow-up period greater than 1 year, about 90% patients achieved protective sensation, while only 10% of the replants presented with diminished cold tolerance and only about 15% with pulp atrophy.…”
Section: Discussionmentioning
confidence: 58%
“…Thus, bone shortening possibly results in poor functional and cosmetic recovery in the replant. Although dissection of a vascular pedicle may preserve the length for vascular repair and some authors performed replantations by dissecting the vessels extensively and using the so-called central branch by transposition to gain the length for direct anastomosis, 20,37,[41][42][43] these methods showed limited reliability. In this series, we compared the survival rate, complications, functional and cosmetic outcomes between fingertip replantations with vein grafting and without vein grafting.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al 2 described a technique of arterial microanastomosis with venous drainage supplied by suturing the deepithelized extremity into the deep abdominal fascia, which has considerably greater vascularization than does the subcutaneous tissue, and reported a high rate of success. Akyürek et al 7 reported distal replantations at zone I by arterial anastomosis alone, with venous drainage by bleeding through an incision in the shape of a "fish mouth" for 7 days or by leech application for 10 to 12 days, with 76% success. Many authors consider leeches to be the best non-surgical treatment for venous insufficiency; however, this technique is not commonly used in Brazil.…”
Section: Discussionmentioning
confidence: 99%